2004
DOI: 10.1021/jp048621s
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electrochemical, and Photophysical Properties of a Molecular Shuttle Attached to an Acid-Terminated Self-Assembled Monolayer

Abstract: Structural, electrochemical, and photophysical properties of a molecular shuttle attached to an acid-terminated self-assembled monolayer Cecchet, F; Rudolf, Petra; Rapino, S; Margotti, M; Paolucci, F; Baggerman, J; Kay, ER; Wong, JKY; Leigh, DA; Kay, Euan R. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 57 publications
10
60
0
1
Order By: Relevance
“…14 The relatively large, negative potentials required to cause switching, however, prevented the operation of such devices on surfaces. 20 Here, we report on a second member of this series, in which a naphthalene-1,4,5,8-diimide station can be switched between three different oxidation states. At each oxidation level, the naphthalene diimide exhibits a different binding affinity for the macrocycle, which leads to a different distribution of rings between two stations in a molecular shuttle.…”
Section: Introductionmentioning
confidence: 99%
“…14 The relatively large, negative potentials required to cause switching, however, prevented the operation of such devices on surfaces. 20 Here, we report on a second member of this series, in which a naphthalene-1,4,5,8-diimide station can be switched between three different oxidation states. At each oxidation level, the naphthalene diimide exhibits a different binding affinity for the macrocycle, which leads to a different distribution of rings between two stations in a molecular shuttle.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is that crown ether molecules form strong complexes with TBA + cations. [76] The presence of the macrocycle does not appear to disrupt the EDL, [77] so the TBA + concentration profile calculated for axle TiO 2 ·2 is also applicable (c.f. Figure 4).…”
Section: Shuttling Of the Crown Ethermentioning
confidence: 99%
“…32 The grafting is achieved because of the formation of hydrogen bonds between the pyridine moiety of the rotaxane molecules and the carboxylic groups at the top of the Au-SAM. Cyclic voltammetric and electrochemical impedance spectroscopic measurements showed that the resulting SAM is densely packed and well ordered, and allowed the estimation of the average thickness of the monolayer.…”
Section: Catenanes and Rotaxanes Immobilized On Surfacesmentioning
confidence: 99%